Relationship between the Management Accounting Information Usage, Market Orientation and Performance: Evidence from Vietnamese Tourism Firms - Huyen Trang Do; Mong Huyen Le; Diem Thuy Thi Luong; Quanh Thi Tran (My University, 2020)
Relationship between the Management Accounting Information Usage, Market Orientation and Performance: Evidence from Vietnamese Tourism Firms
Keywords: Accounting information; Market orientation; Tourism firms